Genetic predisposition for morningness-eveningness and economic disadvantage: Evidence from Finland over 25 years - Hazak, Aaro; Kantojärvi, Katri; Liuhanen, Johanna; Sulkava, Sonja; Jääskeläinen, Tuija; Salomaa, Veikko; Koskinen, Seppo; Perola, Markus; Paunio, Tiina (Elsevier BV, 2026)
Objectives
Individual chronotype may shape economic outcomes through alignment or misalignment with work and societal schedules. Genome-wide association studies suggest that morningness–eveningness has a partially genetic basis. This study examines how genetic predisposition to chronotype relates to economic disadvantage, using polygenic indices for morningness–eveningness both as predictors and as instruments for phenotypic chronotype.
Methods
Employing various regression and extended regression models, we studied data from 20,121 working-aged adults representative of Finnish regions, combining genetic, registry, and survey data from 1992 to 2017.
Results
Genetic markers for morningness were monotonically negatively associated with educational attainment (p = 0.002)—a key determinant of economic success—particularly in males. Conversely, the same genetic markers were also monotonically negatively associated with the likelihood of belonging to the lowest income quintile in males (p = 0.012), suggesting differential valuation of chronotype traits in education versus the labour market. This pattern emerged in post-2000. Furthermore, among males with higher education, genetic predisposition to eveningness was linked to a higher likelihood of falling into the lowest income quintile (p < 0.001), indicating reduced economic returns to their education. No significant associations between chronotype-related genetic markers and income were observed in females across education levels.
Conclusions
This study reveals emerging, gender-specific inequalities in how genetically influenced chronotype traits relate to economic outcomes. Genetic predisposition to eveningness favoured education but hindered income—especially in highly educated males—via phenotypic chronotype pathways. Though modest, these effects highlight the need for workplace inclusion through recognition of chronotype diversity, public sleep health initiatives, and flexible work structures.